PEMBELAJARAN RANDAI MINANGKABAU SEBAGAI STRATEGI DEKOLONISASI KURIKULUM SENI BUDAYA DI SEKOLAH MENENGAH ATAS - Fitriah Azizah; Evindo Marsiano; Jupriani; Indrayuda (STKIP Subang, 2026)
Arts and Culture education in schools continues to be dominated by approaches that emphasize modern artistic knowledge and practices, resulting in limited integration of local traditional arts into the learning process. This condition may reduce students’ understanding of their regional cultural heritage and weaken their awareness of local cultural identity. This article aims to describe the development and initial implementation of Minangkabau Randai learning as a strategy for the decolonization of the Arts and Culture curriculum at the senior high school level. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The initial implementation was carried out through the introduction of Randai and basic galombang movement exercises for students. Data were collected through observation, documentation, and literature review and were analyzed using a qualitative descriptive approach based on the perspectives of critical pedagogy and cultural studies. The findings indicate that Randai has strong potential as a local culture-based learning resource because it integrates elements of theatre, music, dance, oral literature, and Minangkabau cultural values. The initial implementation demonstrated active student engagement in learning and practicing the fundamental elements of Randai. Furthermore, Randai learning provided opportunities for students to understand local culture through direct and contextual learning experiences. Therefore, Randai-based learning can serve as an alternative strategy to support the decolonization of the Arts and Culture curriculum by promoting inclusivity, contextual relevance, and the strengthening of local cultural identity.